2022
DOI: 10.1111/1759-7714.14567
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐organs perioperative immune‐related adverse events and postoperative bronchial anastomotic fistula in a patient receiving neoadjuvant immunotherapy with NSCLC

Abstract: The safety of neoadjuvant chemoimmunotherapy before surgery in patients with non–small cell lung cancer (NSCLC) remains unclear in the perioperative stage. We describe a case of a 63‐year‐old man with IIIC stage NSCLC who received neoadjuvant chemoimmunotherapy and radical lobectomy. After the second cycle of pembrolizumab and chemotherapy (paclitaxel + carboplatin), the patient was diagnosed with immunologic enterocolitis and relieved by glucocorticoid therapy. Radical lobectomy of the right upper lobe was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Ten patients (16.9%) had immune‐related adverse events (irAEs), including rash ( n = 6), immune‐related thyroiditis ( n = 2), immune‐related enteritis ( n = 1) and immune‐related pneumonia ( n = 2). Only one grade 3–4 adverse reaction was observed (see our previous case report) 7 . Two patients’ surgeries were delayed because of irAEs.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Ten patients (16.9%) had immune‐related adverse events (irAEs), including rash ( n = 6), immune‐related thyroiditis ( n = 2), immune‐related enteritis ( n = 1) and immune‐related pneumonia ( n = 2). Only one grade 3–4 adverse reaction was observed (see our previous case report) 7 . Two patients’ surgeries were delayed because of irAEs.…”
Section: Resultsmentioning
confidence: 79%
“…Only one grade 3–4 adverse reaction was observed (see our previous case report). 7 Two patients’ surgeries were delayed because of irAEs.…”
Section: Resultsmentioning
confidence: 99%
“…Concordant with this hypothesis, Zhao et al [18] have published a report of a patient with locally advanced non-small cell lung cancer receiving nivolumab who developed pneumonitis requiring ICU admission 1 week after bilobectomy. Two other similar, albeit milder, cases of ICI-related interstitial lung disease after thoracic surgery for non-small cell lung cancer have been reported [19,20]. Likewise, Sasaki et al [21] have reported a case of ICI-related hypopituitarism and hypothyroidism 4 days after partial hepatectomy for liver metastases in a patient with gastric cancer treated with Fig.…”
Section: Hla-b27 Negativementioning
confidence: 84%
“…In clinical practice, although the incidence of AEs in immunotherapy is often much lower than that in chemotherapy, immune related AEs (such as pneumonitis, myocarditis, etc.) are often challenging to manage and can substantially impact the quality of life ( 35 ). At different periods of this study, it was observed that the incidence of total AEs, grade 3-5 AEs, serious AEs, and fatal AEs was higher in the PIO group than in the PP group in varying degrees, especially during the neoadjuvant treatment phase.…”
Section: Discussionmentioning
confidence: 99%